Report analysing the CSR initiatives of selected Indian IT companies and recommendation of a Regenerative Business Model - Guruswamy, Rathi (2011)
This report captures the corporate social responsibility (CSR) activities of TCS, Infosys and Cognizant - global leaders in the ‘next generation’ of Information Technology (IT) and consulting. The CSR activities captured in this report focus mainly on the current CSR initiatives of the companies as these companies have been practicing CSR for more than 10 years and capturing all the CSR activities will be too broad in the context of this report.The report starts with analysing the CSR initiatives of the selected Indian IT companies. The analysis paves way to find the gaps in the existing strategies of the companies. The internship at BITC aimed to create a business model for businesses in 2050. This naturally involved understanding the current trends and forces that shape business around the world. The trends and forces show how Indian IT companies can capture the opportunities and stay focused by considering the related threats. This data feeds into the creating of a recommended business model – Regenerative Business Model not just for the IT companies but for a wider audience.